THE EFFECT OF GOOD CORPORATE GOVERNANCE ON THE PERFORMANCE OF MEDIUM-SIZED PUBLIC COMPANY IN INDONESIA (Journal of Business and Management, 2021)
Abstract:This research is aimed to examine the relationship between good corporate governance (GCG) and company performance, where medium-sized public companies in Indonesia will be used as the subjects. The samples that are used in this study consist of various public companies in Indonesia which are listed in development board of Indonesia Stock Exchange period 2017-2019. The set of variables that will be used in this study in order to examine the GCG has also been used in numerous similar studies which are board of commissioners, independent commissioner, institutional ownership, and foreign ownership. To measure the company’s performance, return on assets (ROA) of each company for the last three years will be used as the proxies. To examine the relationship between GCG and company performance, panel data analysis test will be used in this research. Based on the test results, it is concluded that foreign ownership has significant negative impact on performance, while the other GCG components (board of commissioners, independent commissioner, and institutional ownership) do not have a significant effect on company performance. This result shows that higher proportion of foreign ownership within the company will decrease company performance.Keywords: good corporate governance (GCG), medium-sized company, company performance (ROA).